Ernst Cassirer as a historian of thought and a philosopher of the affirmation of science (in Polish) (Diametros, 2011)
This paper presents Ernst Cassirer’s critical philosophy and its multidimensionality, which makes it possible link the quantitative methodology of the exact sciences with non-quantitative methodology of the humanities. In the text I undertake the task of presenting the thinker as a neo-Kantian who follows both the mathematical and physical path of Kant and the antinaturalistic path of Geistesgeschichte, as befits Cassirer’s as both a philosopher and a historian of philosophy who builds his own project of the philosophy of culture. I also point to an important issue for Cassirer, the matter of the historic consciousness of Wilhelm Dilthey who allows for the interpretation of the problem of man in the context – as Paczkowska-Łagowska puts it – of the "historical continuity of the tradition".